2007
DOI: 10.1016/j.str.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of PCSK9: A Regulator of Plasma LDL-Cholesterol

Abstract: Proprotein convertase subtilisin kexin type 9 (PCSK9) has been shown to be involved in the regulation of extracellular levels of the low-density lipoprotien receptor (LDLR). Although PCSK9 is a subtilase, it has not been shown to degrade the LDLR, and its LDLR-lowering mechanism remains uncertain. Here we report the crystal structure of human PCSK9 at 2.3 A resolution. PCSK9 has subtilisin-like pro- and catalytic domains, and the stable interaction between these domains prevents access to PCSK9's catalytic sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
205
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(220 citation statements)
references
References 35 publications
13
205
0
2
Order By: Relevance
“…The C-terminal end of the prodomain is occluding the catalytic site (black circle). B. Clustered histidines (labeled) lie on one face of the C-terminal domain, suggesting a potential role in enhancing the affinity of PCSK9 for the LDLR at endosomal pH [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal end of the prodomain is occluding the catalytic site (black circle). B. Clustered histidines (labeled) lie on one face of the C-terminal domain, suggesting a potential role in enhancing the affinity of PCSK9 for the LDLR at endosomal pH [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of PCSK9 at neutral pH has now been reported by two groups, and raises many intriguing new questions about PCSK9 biochemistry and function [29,31]. The two most striking features of the structure are (i) the catalytic site of the enzyme is blocked by the prodomain in a non-covalent complex ( Figure 5A), and (ii) the C-terminal domain, which consists of three beta-domain modules related to one another by a pseudo three-fold axis, displays a surface rich in histidine residues along a stripe derived primarily from the second module ( Figure 5B).…”
Section: Pcsk9 Structurementioning
confidence: 95%
“…The crystal structure study of a full-length construct of PCSK9 established that it binds to the extracellular domain of the LDL receptor [Cunningham et al, 2007;Piper et al, 2007]. The binding site for the LDLR EGF-A domain resides on the surface of PCSK9 that is formed primarily by residues 367 to 381.…”
Section: Impact Of Pcsk9 On the Ldl Receptormentioning
confidence: 99%
“…Finally, the low plasma LDL-C levels and the reduction of CHD displayed in PCSK9 loss-of-function mutation carriers, which seem furthermore healthy, indicate that the inhibition of PCSK9 should be an effective target in the treatment of hypercholesterolemia with no known adverse side effects. The recent elucidation of the crystal structure of PCSK9 [Cunningham et al, 2007;Piper et al, 2007], especially in complex with the LDL receptor [Kwon et al, 2008], should provide essential clues for the identification of small pharmacological molecules or antibodies that might block the interaction of PCSK9 and the LDLR and thus inhibit PCSK9 function and constitute new cholesterol-lowering drugs [Kwon et al, 2008;Grefhorst et al, 2008].…”
Section: Future Prospectsmentioning
confidence: 99%
“…4 Mature PCSK9 is secreted from the cell into circulation. [5][6][7][8] The circulating PCSK9 can bind to LDLR, leading to the co-internalization, followed by the degradation of LDLR. 9 Studies demonstrated that the overexpression of PCSK9 results in depletion of LDLR, and thus a dramatic increase in plasma level of cholesterol.…”
Section: Introductionmentioning
confidence: 99%